TROPHIC STATUS AND FISH YIELD POTENTIAL OF PAHUJ RESERVOIR, UTTAR PRADESH - BANIK, SURAJIT K.; WANGANEO, A.; DAS, A. K. (Journal of the Inland Fisheries Society of India, 2021)
Pahuj, a small reservoir, located at Jhansi in Uttar Pradesh was investigated during April 2006 to March 2009 for evaluating fish yield potential. The reservoir receives a portion of Jhansi city sewage through Pahuj River. As per the physico-chemical parameters, the reservoir has been categorized as eutrophic. Average fish yield during 1994-95 to 2008-09 was 142.03 kg ha-1year-1, whereas during study period (2006-07 to 2008-09) it was 286.43 kg ha-1year-1. The potential fish yield was estimated using morpho-edaphic index, which revealed that the reservoir have potential to produce up to 560.78 kg ha-1year-1. Thus, there is scope for enhancing the fish yield in the reservoir if proper management measures are adopted.Key words: Small reservoir, eutrophication, production potential, fish yield